Advancing mobile learning in Australian healthcare environments: nursing profession organisation perspectives and leadership challenges - Carey Ann Mather; Elizabeth Anne Cummings; Fred Gale (BMC, 2018)
Abstract Background Access to, and use of, mobile or portable devices for learning at point of care within Australian healthcare environments is poorly governed. An absence of clear direction at systems, organisation and individual levels has created a mobile learning paradox, whereby although nurses understand the benefits of seeking and retrieving discipline or patient-related knowledge and information in real-time, mobile learning is not an explicitly sanctioned nursing activity. The purpose of this study was to understand the factors influencing mobile learning policy development from the perspective of professional nursing organisations. Methods Individual semi-structured interviews were undertaken with representatives from professional nursing organisations in December 2016 and January 2017. Recruitment was by email and telephone. Qualitative analysis was conducted to identify the key themes latent in the transcribed data. Results Risk management, perceived use of mobile technology, connectivity to information and real-time access were key themes that emerged from the analysis, collectively identifying the complexity of innovating within an established paradigm. Despite understanding the benefits and risks associated with using mobile technology at point of care, nursing representatives were reluctant to exert agency and challenge traditional work patterns to alter the status quo. Conclusions The themes highlighted the complexity of accessing and using mobile technology for informal learning and continuing professional development. Mobile learning cannot occur at point of care until the factors identified are addressed. Additionally, a reluctance by nurses within professional organisations to advance protocols to govern digital professionalism needs to be overcome. For mobile learning to be perceived as a legitimate nursing function requires a more wholistic approach to risk management that includes all stakeholders, at all levels. The goal should be to develop revised protocols that establish a better balance between the costs and benefits of access to information technology in real-time by nurses.